Pareto-Improving Tax Reforms and the Earned Income Tax Credit - Felix Bierbrauer; Pierre C. Boyer; Emanuel Hansen (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper provides necessary and sufficient conditions for the existence of Pareto-improving tax reforms. The conditions can be expressed as sufficient statistics and have a wide range of potential applications in public finance. We discuss one such application in detail: the introduction of the Earned Income Tax Credit (EITC) in the US. We find that the EITC can be viewed as a response to an in-efficiency in the tax and transfer system prevailing at the time. This adds a new perspective to the literature on why the EITC is a good idea, emphasizing Pareto improvements rather than equity-efficiency trade-offs.
Keywords: C72; D72; D82; H21; 330; tax reforms; non-linear income taxation; optimal taxation; earned income tax credits; pareto efficiency